Targeting HER2 in Nuclear Medicine for Imaging and Therapy - Adriana V. F. Massicano PhD; Bernadette V. Marquez-Nostra PhD; Suzanne E. Lapi PhD (Molecular Imaging, 2018)
Since its discovery, the human epidermal growth factor 2 (HER2) has been extensively studied. Presently, there are 2 standard diagnostic techniques to assess HER2 status in biopsies: immunohistochemistry and fluorescence in situ hybridization. While these techniques have played an important role in the treatment of patients with HER2-positive cancer, they both require invasive biopsies for analysis. Moreover, the expression of HER2 is heterogeneous in breast cancer and can change over the course of the disease. Thus, the degree of HER2 expression in the small sample size of biopsied tumors at the time of analysis may not represent the overall status of HER2 expression in the whole tumor and in between tumor foci in the metastatic setting as the disease progresses. Unlike biopsy, molecular imaging using probes against HER2 allows for a noninvasive, whole-body assessment of HER2 status in real time. This technique could potentially select patients who may benefit from HER2-directed therapy and offer alternative treatments to those who may not benefit. Several antibodies and small molecules against HER2 have been labeled with different radioisotopes for nuclear imaging and/or therapy. This review presents the most recent advances in HER2 targeting in nuclear medicine focusing on preclinical and clinical studies.